Speculative art histories : analysis at the limits - Tuinen, Sjoerd van, 1978- (Edinburgh University Press, 2017)
First full-scale thematic analysis of Pina Bausch's Tanztheater, critically evaluating the impact of modernist theatre on her choreographic method.